RISK OF DEVELOPING SUSTAINED HYPERTENSION IN ISOLATED SYSTOLIC HYPERTENSION OF THE YOUNG IDENTIFIED WITH AMBULATORY BLOOD PRESSURE MONITORING. (June 2018) - Saladini, F.; Fania, C.; Mos, L.; Garavelli, G.; Mazzer, A.; Palatini, P.
Abstract : Objective: Whether isolated systolic hypertension of the young (ISHY) is at increased risk of adverse outcome and should be treated is still debated. Previous data indicate that one of the main determinants of ISHY is a pronounced white-coat effect. The aim of the present study was to examine the risk of developing hypertension needing treatment (HT) in subjects with ISHY diagnosed with ambulatory blood pressure monitoring (ABPM). Design and method: Methods: Among 1206, 18-to-45-year-old, participants from the HARVEST study, we identified 269 subjects with normotension (NT), 209 with ISHY, 277 with isolated diastolic hypertension (IDH) and 451 with systolic-diastolic hypertension (SDH). The 97 mmHg partition value was used to distinguish between subjects with high (= > 97 mmHg) and low 24 h mean BP. The risk of HT, defined according to available International guidelines, was evaluated in multivariable Cox analysis adjusting for several confounders. Results: Compared to the other hypertension subtypes, ISHY participants were younger, more frequently males and more active in sports. They had lower office and 24 h heart rate, lower cholesterol and higher left ventricular stroke volume than the other three groups. During an 11.5-year follow-up, 65.1% of participants developed HT. In multivariate Cox analysis, using the NT group as a reference, the risk of incident HT was 1.29 (1.03–1.61) in IDH and 1.87 (1.53–2.28) in SDH participants, while in ISHY group the risk was not significantly different from that in NT being 1.12 (95%CI, 0.87–1.45). When the ISHY participants were divided according to their 24 h mean BP, only one third showed a high mean BP. The 140 ISHY participants with low mean BP had no increase in risk of HT (0.98, 0.72–1.33), whereas those with high 24 h mean BP had a significant increase in risk (1.74, 1.31–2.30). Conclusions: Subjects with ISHY identified with ABPM are at low risk of developing hypertension needing treatment later in life. The risk is increased only in the minority of ISHY subjects with high 24 h mean BP.